2017
DOI: 10.1097/md.0000000000006156
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis associated with infliximab therapy in ulcerative colitis

Abstract: Rationale:Although immunomodulatory therapy has been clearly stated as an important landmark in treatment of ulcerative colitis, significantly improving the quality of life for patients with inflammatory bowel disease, there are several aspects to be considered regarding the possible side-effects of anti-TNF alpha agents. In spite of a good safety profile, biologic TNF antagonists may induce paradoxical inflammation, which can manifest as sarcoid-like granulomatosis, consisting of noncaseating granulomas in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Oxidized LDL levels found in surgically excised stenotic valves are strongly correlated with the degree of inflammation and fibrocalcic remodelling of the valve [13,14]. Elevated systemic levels of lipoprotein (a) [Lp (a)] and oxidized phospholipids are also associated with AS and its progression [15,16]. Furthermore, it has recently been demonstrated that the LPA gene that codes for apolipoprotein (a) and determines Lp (a) levels is associated with the development and progression of calcific AS, in addition to being a risk factor for cardiovascular diseases [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…Oxidized LDL levels found in surgically excised stenotic valves are strongly correlated with the degree of inflammation and fibrocalcic remodelling of the valve [13,14]. Elevated systemic levels of lipoprotein (a) [Lp (a)] and oxidized phospholipids are also associated with AS and its progression [15,16]. Furthermore, it has recently been demonstrated that the LPA gene that codes for apolipoprotein (a) and determines Lp (a) levels is associated with the development and progression of calcific AS, in addition to being a risk factor for cardiovascular diseases [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…Four common categories of drugs that have been associated with the development of DISR are ICIs[ 2 - 4 ], HAART[ 5 - 7 ], IFNs[ 8 - 10 ], and TNF-α antagonists[ 11 - 13 ]. Also, several drugs such as BRAF[ 14 - 16 ] inhibitors, methotrexate and BCG have been associated with the development of syndromes indistinguishable from sarcoidosis, and are described as DISR.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, SLRs are referred to as Drug Induced Sarcoid-Like Reactions (DISR) [ 91 ]. Other therapies that can induce SLRs include antiretroviral drugs, adalimumab [ 92 ] and infliximab [ 93 ], which, paradoxically, are also potential therapies for sarcoidosis. The exact immunopathogenesis of DISR is currently unknown.…”
Section: Differential Diagnosismentioning
confidence: 99%